Use of Vasoactive Medications after Cardiac Surgery in the United States - Vail, Emily A. (Ann Am Thorac Soc, 2021)
Rationale: Patients undergoing cardiac surgery often require vasopressor or inotropic (“vasoactive”) medications, but patterns of postoperative use are not well described. Objectives: This study aimed to describe vasoactive medication administration throughout hospitalization for cardiac surgery, to identify patient- and hospital-level factors associated with postoperative use, and to quantify variation in treatment patterns among hospitals. Methods: Retrospective study using the Premier Healthcare Database. The cohort included adult patients who underwent coronary artery bypass grafting or open valve repair or replacement (or in combination) from January 1, 2016, to June 30, 2018. Primary outcome was receipt of vasoactive medication(s) on the first postoperative day (POD1). We identified patient- and hospital-level factors associated with receipt of vasoactive medications using multilevel mixed-effects logistic regression modeling. We calculated adjusted median odds ratios to determine the extent to which receipt of vasoactive medications on POD1 was determined by each hospital, then calculated quotients of Akaike Information Criteria to compare the relative contributions of patient and hospital characteristics and individual hospitals with observed variation. Results: Among 104,963 adults in 294 hospitals, 95,992 (92.2%) received vasoactive medication(s) during hospitalization; 30,851 (29.7%) received treatment on POD1, most commonly norepinephrine (n = 11,427, 37.0%). A median of 29.0% (range, 0.0–94.4%) of patients in each hospital received vasoactive drug(s) on POD1. After adjustment, hospital of admission was associated with twofold increased odds of receipt of any vasoactive medication on POD1 (adjusted median odds ratio, 2.07; 95% confidence interval, 1.93–2.21). Admitting hospital contributed more to observed variation in POD1 vasoactive medication use than patient or hospital characteristics (quotients of Akaike Information Criteria 0.58, 0.44, and <0.001, respectively). Conclusions: Nearly all cardiac surgical patients receive vasoactive medications during hospitalization; however, only one-third receive treatment on POD1, with significant variability by institution. Further research is needed to understand the causes of variability across hospitals and whether these differences are associated with outcomes.